Principle of Proportionality X (In) Admissibility of Evidence Obtained by Unlawful Particular in Criminal Proceedings - de Araújo, Dalvaney Aparecida (2016)
The illegal evidence is a flagship in the law and their use is rejected on the constitutional text. The doctrine and jurisprudence study the institute enforcement mechanisms and in which cases would be appropriate to the use of theory. Analyzes the theory of illegal evidence, the principle proportionality and the jurisprudence of the Supreme Court in order to show that the sealing of the use of illegal evidence is limited both to public bodies responsible for criminal prosecution as well as to individuals. That by virtue of the guarantee fundamental rights and legal security measure. We used the deductive method.